Differential Object Marking, Case and Agreement - Ormazabal, Javier; Romero, Juan (Borealis – An International Journal of Hispanic Linguistics, 2013)
In this paper, we present empirical evidence showing that Differential Object Marking (DOM) in Spanish is determined by structural conditions related to Case and agreement. We also argue that semantic concepts such as specificity, definiteness, animacy, or topicality, tightly connected to the presence or absence of A, must be parasitic on the syntactic configurations where DOM is licensed. We also present some consequences of our analysis for the general theory of agreement. We argue that the same structural relation is involved in all cases of DOM, as well as in Dative Clitic Constructions, where the presence of the particle A preceding clitic-doubled datives is syntactically unified with DOM phenomena. The accusative/dative distinction traditionally attributed to the Spanish pronominal system does not correspond, in synchronic terms, to different case relations, but distinguishes between agreeing and non-agreeing arguments. Similarly, the distribution of DOM corresponds to a Case-checked/Caseless difference. We extend the analysis to account for well-known restrictions on the co-appearance of two DOM arguments, which are analyzed as the consequence of a competition between two arguments for a single target.